Implementation of Cloud-Based Management Information System in Improving Operational Efficiency of Logistics Sector Companies - Anggun Lestari, Dea (Arbain Publishing, 2024)
This study aims to analyze the implementation of cloud-based management information systems in improving operational efficiency in logistics sector companies. Along with technological developments, logistics companies face challenges in managing increasingly complex data and operations. The implementation of cloud-based systems offers a solution to simplify the process by increasing flexibility, speed of access, and reducing IT infrastructure costs. This study uses a qualitative method with a literature study and library research approach. Data is collected through literature reviews involving various sources such as journal articles, books, and industry reports related to the implementation of cloud systems in the logistics sector. An analysis of the literature shows that companies that implement cloud-based systems have successfully improved operational efficiency through reduced processing times, workflow automation, and better collaboration capabilities between teams. In addition, cloud-based systems also allow companies to manage data in a more secure and structured manner. However, the study also found several challenges, such as data security risks and reliance on a stable internet network. Therefore, the successful implementation of a cloud-based management information system is highly dependent on good infrastructure readiness and risk management. The results of this research are expected to contribute to the development of cloud system implementation strategies in the logistics sector, as well as provide guidance for companies in maximizing operational efficiency through information technology.